Enhanced oil recovery monitoring for oilfield produced water treatment using rotating ceramic membranes - Schnabel, B.; Ebrahimi, M.; Schmitz, O.; Kerker, S.; Hild, J.; Gutmann, C.; Aden, M.; Liebermann, F.; Czermak, Peter (My University, 2013)
The study at hand focuses on an investigation about the effects of membrane rotational speed (MRS) and transmembrane pressure (TMP) on the performance of dynamic cross flow ultrafiltration while treating oily wastewater. The experimental area ranged from 600 to 1800 rpm towards the MRS and 0.5 to 1.5 bar towards the TMP. The quality indication of the filtration performance used in this study was the permeate flux as well as the total organ carbon (TOC) and oil rejection. The results show that there is a positive effect of the investigated process parameters MRS and TMP on the permeate flux within the investigated range. The permeate flux increased 3.7 fold from 39 to 144 l h-1 m-2 while increasing the MRS and 2.2 fold from 83 to 183 l h-1 m-2 while increasing the TMP within the investigated range. The used 7 nm ceramic membrane disc showed high oil rejection efficiency: the calculated TOC rejection values ranged from 87 to 96 % and the oil rejection values were all > 99 %. Further more the AFGUARD® sensor, which is an optical sensor and primary used for the measurement of water in fuel, was tested for the application of measuring oil in water. We could observe a high correlation of the sensor output signal and an oily model solution (OMS) in the range of 0 to 100 ppm TOC.
Keywords: Online monitoring; Optical measurements; Produced water treatment; Rotating ceramic filter discs; Dynamic cross-flow filtration; Ultrafiltration